Shortening of the European Dauphinois margin (Oisans Massif, Western Alps): New insights from RSCM maximum temperature estimates and 40Ar/39Ar in situ dating. (January 2015) - Bellanger, M.; Augier, R.; Bellahsen, N.; Jolivet, L.; Monié, P.; Baudin, T.; Beyssac, O.
Highlights: Maximum temperatures ( T max ) were measured in cover series using the RSCM method. T max are close to 335 °C from Belledonne to the Penninic Frontal Thrust. Chlorite geothermometry yielded consistent ca. 300–350 °C temperature for peak-conditions within the basement. The timing of the activity of Alpine shear zones was constrained by using 40 Ar/ 39 Ar dating on synkinematic phengites. Deformation localized progressively within high-strain rocks within shear zones (phyllonites) between 33 and 25 Ma. Abstract: The Oisans Massif, located in the external zones of the western Alps, experienced significant shortening during the Alpine collision. While a series of major top-to-the west shear zones was recently described, the general low grade of the metamorphism has not attracted much petrological and geochronological studies. This paper provides combined temperature and age constraints on the evolution of the Oisans Massif. Temperature was estimated with the Raman Spectrometry of Carbonaceous Material (RSCM) method and chlorite geothermometry. Maximum temperature reached by the Mesozoic cover ( T max ) from Grenoble to the Galibier pass (E-W) and from Saint Jean de Maurienne to Embrun (N-S) yielded almost constant ca. 330 °C temperatures all through the Massif. Temperatures however strongly decrease either westward towards the top of the Vercors sedimentary sequence or eastward towards the Penninic Frontal Thrust. Age constraints were retrieved using 40 Ar/ 39 Ar in situ analyses performed on variously strained samples from Alpine shear zones. Over strain gradients, incipient Alpine recrystallizations progressively develop at the expense of former Variscan parageneses. A combined textural and EPMA approach permitted to identify newly formed chlorite and phengite that unequivocally grew in response to deformation or to low grade metamorphism. Chlorites recorded temperatures from ca. 350–150 °C during the activity of shear zones. In parallel, 40 Ar/ 39 Ar in situ experiments enabled dating deformation using both synkinematic phengites crystallized below the closure temperature of white-micas and former Variscan muscovite whose isotopic system have been, at least partially re-opened. Activity of top-to-the-west shear zones responsible for the shortening and thickening of the Oisans massif thus occurred between 34 and 33 and 25 Ma. Integrating these new age-constraints, T max estimates, and published geological data on the Oisans Massif and neighbouring areas allow proposing a new shortening scenario for the external zones. From ca. 34–33 Ma, the Oisans Massif was buried as a rigid block below more internal units and reached a temperature of ca. 330 °C. Shearing progressively localized along a series of top-to-the-W shear zones in the basement until 25 Ma. Deformation then localized along a major thrust at the base of the ECM massif and propagated along the basement-cover interface below the Vercors massif after 16 Ma.